Crystallization of hollow mesoporous silica nanoparticles. Issue 20 (11th December 2014) - Drisko, Glenna L.; Carretero-Genevrier, Adrian; Perrot, Alexandre; Gich, Martí; Gàzquez, Jaume; Rodriguez-Carvajal, Juan; Favre, Luc; Grosso, David; Boissière, Cédric; Sanchez, Clément
Abstract : Amorphous structured silica can now be crystallized to pure α-quartz under relatively mild conditions, while preserving initial complex architectures. Abstract : Complex 3D macrostructured nanoparticles are transformed from amorphous silica into pure polycrystalline α-quartz using catalytic quantities of alkaline earth metals as devitrifying agent. Walls as thin as 10 nm could be crystallized without losing the architecture of the particles. The roles of cation size and the mol% of the incorporated devitrifying agent in crystallization behavior are studied, with Mg 2+, Ca 2+, Sr 2+ and Ba 2+ all producing pure α-quartz under certain conditions.